Frankenstein A New Edition for Scientists and Engineers - Finn, Ed; Guston, David; Guston, Robert; Scott, Jason; Shelley, Mary (The MIT Press, 2017)
This new critical edition of Mary Shelley's Frankenstein was developed by leading scholars for aspiring scientists, engineers, and medical professionals. This unique framing will make this a core text in promoting and enhancing interdisciplinary dialogue on the nature, roles, and responsibilities of scientists and engineers in society. To be published in time for the 2018 bicentennial of its original publication, this edition will be produced in print and as an enhanced e-book. The e-book will contain the full text of the novel (in the public domain) plus all of the substantial scholarly material that was commissioned and developed for this new edition, including essays by leading scholars, and will be most valuable to students and teachers of ethics. Digital features will include include reader annotation, bookmarking, and multimedia content.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Fiction; Fiction; Electronic books